2019
DOI: 10.1186/s13063-019-3499-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of exercise training on cardiotoxicity and cardiac health outcomes in women with breast cancer anthracycline chemotherapy: a study protocol for a randomized controlled trial

Abstract: Background Anthracyclines are chemotherapeutic agents frequently used in breast cancer (BC) treatment. Although it improves disease-free and overall survival, the use of anthracyclines is associated with a cumulative risk of cardiac toxicity. Preventive strategies to optimize cardiac health are needed and exercise is proposed as a potential non-pharmacological approach for counteracting anthracycline-related cardiotoxicity (ARC). Most of the data on the effects of exercise to reduce ACT are from a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Therefore, additional research is needed to identify a safe and optimal dose of FITT (frequency, intensity, time, type) prescription to target this issue. We identified ten ongoing trials [27,36] and four published study protocols [37][38][39][40] which are exploring this topic and their results might help to address some research gaps in a near future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, additional research is needed to identify a safe and optimal dose of FITT (frequency, intensity, time, type) prescription to target this issue. We identified ten ongoing trials [27,36] and four published study protocols [37][38][39][40] which are exploring this topic and their results might help to address some research gaps in a near future.…”
Section: Discussionmentioning
confidence: 99%
“…Four unique RCTs [23][24][25][26] were included (Table 1). Furthermore, we identified ten ongoing trials [27][28][29][30][31][32][33][34][35][36] and four published study protocols [37][38][39][40] that appear to meet the predefined PICO criteria (Supplementary Material Table S2).…”
Section: Study Selectionmentioning
confidence: 99%
“…In fact, the primary prescription of RT within the literature, to date, is exclusively coupled with AE. Moreover, it is hypothesized that an exercise program consisting of a combined prescription of both AE and RT may induce favorable physiological outcomes when compared to either modality prescribed independently [57][58][59]. To evaluate the application of combination training in BC populations, a randomized controlled trial by Cornette et al sought to investigate the effects of a two-arm prospective home-based exercise program consisting of both aerobic and RT prescribed to a BC population (Table 4).…”
Section: Combinational Effects Of Aerobic Exercise and Resistance Training On Ctrcdmentioning
confidence: 99%
“…Furthermore, another clinical trial (ISRCTN32617901) is currently taking place to demonstrate the impact of PA (3 days per week with progressive volume and intensity during the period of treatment) on anthracycline-derived cardiotoxicity medical care. Multiple variables will be studied, including biochemical, physiological, and psychological parameters [ 161 ]. Even from an acute dose, PA seems to prevent and improve cardiovascular function prior to chemotherapy, as demonstrated by Kirkham et al [ 162 ], who observed a wide multitude of positive effects of 30 min duration PA only 24 h before doxorubicin treatment, including echocardiographic, serological, and physiological parameters.…”
Section: Pa In Bc Managementmentioning
confidence: 99%